The New Penal Law of the Church - Sánchez-Girón Renedo, José Luis (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2021)
The new Book VI aims to further promote the application of canon criminal law. There are canons that clearly have this meaning, others that have been reworked with the same intention, and the wording tries to be clearer by defining the better the steps that have to be taken. The number of crimes increases (those of a sexual nature have an important precedent in the m. p. Vos estis lux mundi), the regulation of the penalty’s remission is more rigorous, optional penalties are notably reduced, and there is an increase of the statute of limitations. All this hardens the criminal discipline with respect to the 1983 CIC. On the other hand, criminal law becomes more applicable to the laity, and the requirement to repair the damage that the crime may generate is underlined.